Employee retention for economic stabilization: A qualitative phenomenological study in the hospitality sector - Dario Vasquez (International Journal of Management, Economics and Social Sciences (IJMESS), 2014)
Focusing on employee retention is vital to increase organizational performance and strengthen a nation's economy. Employee turnover leads to high unemployment and slow economic growth around the globe. The purpose of this study was to explore the reasons and motivating factors that cause employees to remain in hospitality despite the high turnover rate in the industry. The data for this study were collected using semi-structured interviews, conducted with hospitality employees in South Florida. The study employed a qualitative phenomenological method to acquire the lived experiences of participants. The findings were in accord with the employee retention approach. The findings revealed that creating a good working environment including management support, reward, and incentive programs would lead to employee retention in the hospitality sector.
Keywords: J53; J63; M21; 330; Employee turnover; employee retention; economic benefits; retention strategies; Hospitality industry